2007
DOI: 10.1083/jcb.200609161
|View full text |Cite
|
Sign up to set email alerts
|

Grd19/Snx3p functions as a cargo-specific adapter for retromer-dependent endocytic recycling

Abstract: Amajor function of the endocytic system is the sorting of cargo to various organelles. Endocytic sorting of the yeast reductive iron transporter, which is composed of the Fet3 and Ftr1 proteins, is regulated by available iron. When iron is provided to iron-starved cells, Fet3p–Ftr1p is targeted to the lysosome-like vacuole and degraded. In contrast, when iron is not available, Fet3p–Ftr1p is maintained on the plasma membrane via an endocytic recycling pathway requiring the sorting nexin Grd19/Snx3p, the pentam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
193
0
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 160 publications
(212 citation statements)
references
References 66 publications
(99 reference statements)
8
193
0
7
Order By: Relevance
“…The retromer complex and the sorting nexin Snx3 function together in an endocytic recycling pathway to maintain the Fet3-Ftr1 high-affinity iron transporter at the plasma membrane at steady state when cells are starved for iron (Strochlic et al, 2007). Snx3 functions as a cargo-specific adapter in this pathway, binding both to a recycling signal in Ftr1 and to the retromer complex.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The retromer complex and the sorting nexin Snx3 function together in an endocytic recycling pathway to maintain the Fet3-Ftr1 high-affinity iron transporter at the plasma membrane at steady state when cells are starved for iron (Strochlic et al, 2007). Snx3 functions as a cargo-specific adapter in this pathway, binding both to a recycling signal in Ftr1 and to the retromer complex.…”
Section: Resultsmentioning
confidence: 99%
“…Vps26p, Vps29, and Vps35 comprise the cargo-recognition subcomplex of retromer, and the structure of the Vps29-Vps35 interface has recently been solved (Hierro et al, 2007). We and others have shown that another sorting nexin, Snx3/Grd19, associates with retromer and is necessary for retromer-dependent trafficking of a subset of retrograde cargo (Hettema et al, 2003;Restrepo et al, 2007;Strochlic et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations